Prehistoric and recent mass movements of the World Cultural Heritage Site Hallstatt, Austria - Rohn, Joachim; et al. (Environmental Geology, 2005)
Hallstatt Village, located in the Austrian Alps, is designated by the United Nations Educational, Scientific and Cultural Organization as part of the World Cultural Heritage Site "Hallstatt-Dachstein". This region is recognized for its salt deposits that have been exploited since the Neolithic period. In former times, these salt deposits were very rare and precious. Due to unfortunate bedding conditions, mass movements have been frequent in the past and continue to affect the site today. These active and inactive mass movements were mapped geotechnically to a scale of 1:5,000 and the mineralogical and mechanical properties of the main instable soft rocks were investigated. Rock spreads, rock slides, rock falls, rock topples, earth flows and earth and debris slides are the primary types of mass movements recorded. They are most frequently observed in areas affected by mining, though they may also occur in areas where no anthropogenic influence is recognized. Evidence exists in the archaeological record that indicates prehistoric mining activities were also seriously affected by the impact of mass movements. © Springer-Verlag 2005.
UnivIS-Import:2015-04-14:Pub.2005.nat.dgeo.IGM.profes_3.prehis
Keywords: Archaeological site; Austria; Cultural Heritage; Earth flow; Hallstatt; Hazard; Landslide; Northern Calcareous Alps